Heracleifolinosides A–F, New Triterpene Glycosides from Cimicifuga heracleifolia, and Their Inhibitory Activities against Hypoxia and Reoxygenation - Liu, Yan-Ru; Wu, Zhi-Jun; Li, Chun-Tong; Xi, Feng-Min; Sun, Lian-Na; Chen, Wan-Sheng (Planta Medica, 2013)
Six new 9,19-cycloartane triterpene glycosides, heracleifolinosides A–F (1–6), and one new chromone, norkhelloside (7), were isolated from the rhizome of Cimicifuga heracleifolia, together with 15 known compounds (8–22). The structures of the new compounds were elucidated by means of spectroscopic methods including 2D NMR and mass spectrometry. The extracts of C. heracleifolia and all the isolated compounds were tested for activities against hypoxia and reoxygenation injury in human umbilical vein endothelial cells. Heracleifolinoside B (2) is effectively resistant to hypoxia and reoxygenation-induced human umbilical vein endothelial cell injury, with cell viabilities of 61.95 ± 2.04 %, 77.04 ± 4.44 %, and 83.65 ± 3.29 % at concentrations of 1, 10, and 100 µM, respectively.
Keywords: Cimicifuga heracleifolia; Ranunculaceae; 9,19-cycloartane triterpene bisglycosides; hypoxia; reoxygenation